ÍCONES DIGITAIS DA FERRAMENTA DE AUTORIA DE OBJETO DE APRENDIZAGEM CACURIÁ: uma proposta - Pontes, Jesiel de Sales (2015)
This study aims to propose digital icons for learning object authoring tool Cacuriá, for the creation of Learning Objects for iDTV (digital TV) and Web site of the Federal University of Maranhão (UFMA) in AVA (a virtual learning framework). The present research work was based on the guidelines of Informational Ergonomics applying a Production Test and a Comprehensive Test. Following this approach, concepts were investigated involving learning objects, informational ergonomics and digital icons. Parameters were used for analysis of typographic elements and readability of icons represented in the applications of the tests according to criteria required by ANSI Z535.3. As the final result, the present work proposes a set of seven digital icons for the graphical interface of the Cacuriá tool based on Production Tests of 72 UFMA students of Pedagogy, Mathematics, Chemistry and Design. The Comprehensive Test involved 100 students, also UFMA students Course Bachelor in Interdisciplinary Science and Technology. Summarizing the different applications, over 172 individuals participated the production tests.